Kesaksian Wanita dalam Pandangan Ulama Tafsir - Anshori Anshori (AHKAM : Jurnal Ilmu Syariah, 2013)
Abstract: Women’s Testimony in View of ‘Ulamâ’ of Tafsîr. Within Islamic law, the testimony of women is controversial. There are those who distinguish between female witnesses and males in matters such as debts, but there also those who equate the two. The difference appears to have resulted from the difference in points of view. Actually when differentiated between al-ishhâd (out of court testimony) and al-shahâdah (testimony) as evidence brought before a judge in court, does not need to distinguish between the testimonies of women and men. Shahâdah in court is determined by the judges, as drawn out by the Prophet and accepting the testimony of a woman in the case of rape. Similarly, the Prophet accepted the testimony of a woman in the case of ‘Uqbah ibn al-Harîth who married Umm Yahyâ bint Abî Lahab.Keywords: al-ishhâd, al-shahâdah, shâhidayn, debtsAbstrak: Kesaksian Wanita dalam Pandangan Ulama Tafsir. Dalam hukum Islam, terjadi kontroversi tentang kesaksian perempuan. Ada yang membedakan antara saksi perempuan dengan laki-laki seperti dalam masalah utang- piutang, tapi ada juga yang menyamakan antara keduanya. Perbedaan tersebut tampaknya diakibatkan oleh perbedaan sudut pandang. Sebenarnya bila dibedakan antara al-ishhâd (memberi kesaksian di luar pengadilan) dan al-shahâdah (persaksian) sebagai alat bukti di depan hakim di pengadilan, tidak perlu membedakan antara kesaksian perempuan dan laki-laki. Shahâdah di pengadilan ditentukan oleh keyakinan hakim, sebagaimana dicontohkan oleh Nabi dengan menerima kesaksian seorang perempuan dalam kasus pemerkosaan. Begitu juga Nabi menerima kesaksian seorang perempuan dalam kasus ‘Uqbah ibn al-Harîth yang mengawini Umm Yahyâ bint Abî Lahab.Kata Kunci: al-ishhâd, al-shahâdah, shâhidayn, utang-piutang.DOI: 10.15408/ajis.v13i2.942